2022
DOI: 10.2147/jmdh.s381151
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance and Associated Factors Among College Students in Dessie City, Northeastern Ethiopia

Abstract: Background The COVID-19 vaccine is regarded as an effective measure for reducing the pandemic’s impact. But, COVID-19 disease burden reduction efforts are being affected by the rising vaccine resistance. Objective To assess the COVID-19 vaccine acceptance and associated factors among college students in Dessie city, Northeastern Ethiopia. Methods An institutional-based cross-sectional study was carried out among college students in Dessie tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
(112 reference statements)
3
7
0
Order By: Relevance
“…These results are consistent with other studies that have reported associations between vaccination willingness and factors such as profession type, education level, and marital status [12]. Previous research has suggested that being married, highly educated, experienced, or a doctor is all associated with better perception, attitude, and willingness to take up COVID-19 vaccines [4,9,10,12,16,29,30], which is in line with our findings. It is possible that these demographic characteristics are linked to higher levels of knowledge, responsibility, and concern for family, which may contribute to greater acceptance of vaccines.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with other studies that have reported associations between vaccination willingness and factors such as profession type, education level, and marital status [12]. Previous research has suggested that being married, highly educated, experienced, or a doctor is all associated with better perception, attitude, and willingness to take up COVID-19 vaccines [4,9,10,12,16,29,30], which is in line with our findings. It is possible that these demographic characteristics are linked to higher levels of knowledge, responsibility, and concern for family, which may contribute to greater acceptance of vaccines.…”
Section: Discussionsupporting
confidence: 93%
“…Also the opinion that vaccination could prevent COVID-19 increased the odds of accepting vaccination, consistent with a previous study from Ethiopia. 28 Employees considering COVID-19 a severe disease were more likely to accept vaccination, in line with a previous report from Ethiopia 13 and numerous other studies.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, very low vaccine acceptance rates were recorded among transportation workers. The vaccination rate in other studies were 39% in Ghana; 20 56.2% in Dessie, Ethiopia; 13 65% in Wollega, Ethiopia; 21 and 73% in southwest Ethiopia. 14 It seems that the vaccination rate in Ethiopia is better than the rate intending to get vaccinated among the employees in this study.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, it is necessary to promote the Covid-19 vaccination in healthcare practitioners to raise awareness of the importance, safety and efficacy of the Covid-19 vaccine and focus on populations at higher risk of contracting the disease. 2…”
mentioning
confidence: 99%